Predictive role of erythrocytes in assessment of COVID-19 outcomes - Yuri N. Smolyakov; Boris I. Kuznik; Elena V. Fefelova; Lyudmila S. Kazantseva; Yuri K. Shapovalov; Maria S. Lukyanchuk; Sergey A. Lukyanov; Konstantin G. Shapovalov (Вопросы вирусологии, 2023)
Introduction. The search for affordable and accurate predictors of the outcome of COVID-19 is extremely important, as it provides the possibility to effectively correct the patient treatment tactics.